FRASA VERBAL ENDOSENTRIK ATRIBUTIF BAHASA BALI ATTRIBUTIVE ENDOCENTRIC VERBAL PHRASES IN BALINESE - Ida Ayu Putu Aridawati (Widyadari : Jurnal Pendidikan, 2021)
This paper addreses the linear structure of attributive endocentric verbal phrases in Balinese. The problems studied include (1) the core element of verbal phrase, as an important element in determining the distribution and composition of Balinese verbal phrases and (2) the linear sequence of additonal elements that are more than one piece, both in one group and in other different groups.The purpose of this study is to obtain a description of the attributive endocentric verbal phrases in Balinese. The theory used as references in this study are the structural theory, that is the concept of syntagmatic relationship and paradigmatic relationship. The method used is descriptive synchronic method and distributional method. The result of the discussion show that the attributive endocentric verbal phrases rely on two things, namely the core element in the form of a verb or verb as an important element in determining the distribution and the linear order of additional elements that are more than one (either in one or more groups). The core elements of Balinese verbal phrases can be classified based on their syntactic meaning, the presence of accompanying objects and the quality of their actions. Additional elements of attributive endocentric verbal phrases in Balinese can be divided into: double additional elements and a combination of three additional elements.